Compatibly bi-Hamiltonian superconformal analogs of Lax-integrable nonlinear dynamical systems - Hentosh О. Ye. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
Compatibly bi-Hamiltonian superanalogs of the known Lax-integrable nonlinear dynamical systems are obtained by using a relation for the Casimir functionals of central extensions of the Lie algebra of superconformal even vector fields and its adjoint semidirect sum.